2001
DOI: 10.1093/emboj/20.17.4639
|View full text |Cite
|
Sign up to set email alerts
|

Activation of integrins in endothelial cells by fluid shear stress mediates Rho-dependent cytoskeletal alignment

Abstract: Fluid shear stress is a critical determinant of vascular remodeling and atherogenesis. Both integrins and the small GTPase Rho are implicated in endothelial cell responses to shear but the mechanisms are poorly understood. We now show that shear stress rapidly stimulates conformational activation of integrin avb3 in bovine aortic endothelial cells, followed by an increase in its binding to extracellular cell matrix (ECM) proteins. The shear-induced new integrin binding to ECM induces a transient inactivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
533
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(571 citation statements)
references
References 52 publications
34
533
4
Order By: Relevance
“…We verified that exposure of EC to 48 h of 8-10 dyn/cm 2 sinusoidal WSS stimuli induced cell elongation and alignment and reorganization of cell monolayer. The EC elongation, previously reported by other groups (Remuzzi et al 1984;Tzima et al 2001), demonstrates the capability of the CPD to induce flow-dependent cell morphological adaptations. In addition, the capability of the system to induce flow-dependent morphological adaptations has been further verified by exposing HUVECs to the atheroprotective and atheroprone WSS waveforms, as calculated in a model of the carotid bifurcation (Dai et al 2004).…”
Section: Discussionsupporting
confidence: 71%
“…We verified that exposure of EC to 48 h of 8-10 dyn/cm 2 sinusoidal WSS stimuli induced cell elongation and alignment and reorganization of cell monolayer. The EC elongation, previously reported by other groups (Remuzzi et al 1984;Tzima et al 2001), demonstrates the capability of the CPD to induce flow-dependent cell morphological adaptations. In addition, the capability of the system to induce flow-dependent morphological adaptations has been further verified by exposing HUVECs to the atheroprotective and atheroprone WSS waveforms, as calculated in a model of the carotid bifurcation (Dai et al 2004).…”
Section: Discussionsupporting
confidence: 71%
“…β1‐Integrin‐containing focal adhesions (FAs) have been shown to be important for shear stress mechanotransduction (Davies et al , 1994; Tzima et al , 2001), and changes in their size and number are regulated in response to the intensity of the mechanical load, thereby controlling the strength of adhesion (Jalali et al , 2001). However, few studies have examined FA in vivo (van Geemen et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies using HUVECs or BAEC plated onto fibronectin have shown that endothelial cells modulate the avidity and affinity of adhesion complexes upon increased shear stress, which results in increased adhesion strength and intracellular signalling (Urbich et al , 2000; Jalali et al , 2001; Tzima et al , 2001). This is consistent with the small adhesion complexes observed in the endothelium of Tek‐Cre::Lama5 −/− arteries, which lack laminin 511 and have a reduced shear stress response, and the larger adhesion complexes in Lama4 −/− vessels, which express laminin 511 and have an enhanced response to shear stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This force is transmitted through the cytoskeleton to FAs. Integrins have been shown to respond to fluid flow (Tzima et al, 2001) and to be locally activated at the downstream edge (Goldfinger et al, 2008). However, this may be due to increased integrin-ECM ligation.…”
Section: Introductionmentioning
confidence: 99%